PERBAIKAN KARAKTERISTIK KAYU KELAPA HIBRIDA MELALUI METODE PEMANASAN DAN PEMADATAN - . Suhasman; Sucahyo Sadiyo; Zahrial Coto (PERENNIAL, 2009)
For optimum utilization of coconut wood, there are necessity to improve the quality of the wood caused by higroscopicity, low dimensional stability, and extreme variability of dimension in lateral direction. The purpose of the research were to analyze the characteristics of coconut wood that had been treated by heating and densification. The treatment consist of one or two hours heating, one hour heating combined to 10 or 20% densification, two hours heating combined to 10 or 20% densification. Temperature that applied for all specimen were 180 oC. The research results are as follows: (1) Heating treatment combined to densification effective to reduce higroscopicity of coconut wood, (2) Heating treatment for two hours are suffice as pretreatment to densify the soft part of coconut wood for 20%, (3) Dimensional stability of coconut wood may improve using heating combined to densification treatments that indicated by decreasing rate of dimensional change, (4) Heating and densification treatment effective to improve the hardness of soft part coconut wood. Keywords : coconut wood, heating treatment, densification References